Expression analysis of candidate genes regulating successional tooth formation in the human embryo - Olley, Ryan; Xavier, Guilherme M.; Seppala, Maisa; Volponi, Ana A.; Geoghegan, Fin; Sharpe, Paul T.; Cobourne, Martyn T. (Frontiers in Physiology, 2014)
Human dental development is characterized by formation of the primary teeth, which are subsequently replaced by the secondary dentition. The secondary dentition consists of incisors, canines and premolars derived from the successional dental lamina of the corresponding primary tooth germs; and molar teeth, which develop as a continuation of the dental lamina. Currently, very little is known about the molecular regulation of human successional tooth formation. Here, we have investigated expression of three candidate regulators for human successional tooth formation; the Fibroblast Growth Factor-antagonist SPROUTY2, the Hedgehog co-receptor GAS1 and the RUNT-related transcription factor RUNX2. At around 8 weeks of development, only SPROUTY2 showed strong expression in both epithelium and mesenchyme of the early bud. During the cap stage between 12-14 weeks, SPROUTY2 predominated in the dental papilla and inner enamel epithelium of the developing tooth. No specific expression was seen in the successional dental lamina. GAS1 was expressed in the dental papilla and follicle, and associated with mesenchyme adjacent to the primary dental lamina during the late cap stage. In addition, GAS1 transcripts were identifiable in mesenchyme adjacent to the successional lamina, particularly in the developing primary first molar. For RUNX2, expression predominated in the dental papilla and follicle. Localized expression was seen in mesenchyme adjacent to the primary dental lamina at the late cap stage; but surprisingly, not in the early successional lamina at these stages. These findings confirm that SPROUTY2, GAS1 and RUNX2 are all expressed during early human tooth development. The domains of GAS1 and RUNX2 are consistent with a role influencing function of the primary dental lamina but only GAS1 transcripts were identifiable in the successional lamina at these early stages of development.